Cymbal synthesiser / Abdul Halim Ali and Ahamad Zabhlul Badiu Zaman - Ali, Abdul Halim; Badiu Zaman, Ahamad Zabhlul (1985)
The objective of building this project is to reproduce of all the fascinating sounds that can be used using a cymbal. As it is a musician's badaet, it would tremendously help to the musician to expand his creativity in the field of music. Secondly, the project will also investigate other methods of controlling basic synthesiser circuit, which generally is used with keyboard, in which the key contact in keyboard is, the easiest method of implementing the switching.